1998
DOI: 10.1007/s001250051007
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and characteristics of silent cerebral infarction in elderly diabetic patients: association with serum-soluble adhesion molecules

Abstract: It has been widely accepted that the initial steps in the formation of atherosclerotic lesions involve the adherence of circulating leukocytes to dysfunctional endothelium and their subsequent transmigration into the arterial intima [1±3]. The recruitment of leukocytes into the tissues is dependent on a multistep cascade of events mediated by distinct adhesion molecules such as the selectin family, immunoglobulin superfamily and integrin family [3,4]. Substantially, vascular cell adhesion molecule-1 (VCAM-1) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
38
0
3

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 47 publications
(39 reference statements)
6
38
0
3
Order By: Relevance
“…The risk increase did not vary with time. In accordance with previous studies, we showed sVCAM-1 levels to be significantly associated with male sex, age, fasting insulin levels, vWF level, the presence of type 2 diabetes, hypertension, and microalbuminuria, and, inversely, with levels of total, LDL, and HDL cholesterol and estimates of glomerular filtration rate (18,(20)(21)(22)27,37). These variables, however, did not materially affect the association between sVCAM-1 levels and risk of cardiovascular mortality (Ta b l e 3).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The risk increase did not vary with time. In accordance with previous studies, we showed sVCAM-1 levels to be significantly associated with male sex, age, fasting insulin levels, vWF level, the presence of type 2 diabetes, hypertension, and microalbuminuria, and, inversely, with levels of total, LDL, and HDL cholesterol and estimates of glomerular filtration rate (18,(20)(21)(22)27,37). These variables, however, did not materially affect the association between sVCAM-1 levels and risk of cardiovascular mortality (Ta b l e 3).…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with previous findings (20,(24)(25)(26)(27)(28)(29), we demonstrated levels of sVCAM-1 to be higher among diabetic than among nondiabetic subjects, suggesting a stronger stimulation of VCAM-1 synthesis among diabetic as compared with nondiabetic subjects. In an environment with long-standing high glucose concentrations, lipids and proteins will undergo nonenzymatic glycation and oxidation, resulting in the successive formation of successively reversible Amadori products (such as GHb) and irreversible metabolites, so-called advanced glycated end products (AGEs) (48,49).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Elevated levels of various cellular adhesion molecules including E-selectin and vascular cell adhesion molecule 1 (VCAM-1) are considered putative markers of endothelial dysfunction. These cellular adhesion molecules are typically elevated in individuals at risk for T2DM, and they are elevated further in diabetic patients who have had silent cerebral infarction (Kawamura et al 1998). A recent longitudinal study in T2DM patients (Stehouwer et al, 2002) indicated that endothelial dysfunction and inflammation progress together over time, each influencing the other and creating a vicious downward spiral.…”
Section: Discussionmentioning
confidence: 99%